Geochemical evidence for provenance diversity of loess in southern China and its implications for glacial aridification of the northern subtropical region. (15th May 2019) - Han, Long; Hao, Qingzhen; Qiao, Yansong; Wang, Luo; Peng, Shuzhen; Li, Nan; Gao, Xinbo; Fu, Yu; Xu, Bin; Gu, Zhaoyan
Abstract: The thick ' Xiashu loess' in southern China is distributed not only in the Yangtze River valley, but also and most extensively in the region between the Qinling Mountains and the lower reaches of the Yangtze River. However, there are few studies of the provenance and climatic implications of the Xiashu loess in this latter region. Here we present the results of a provenance study of Last Glacial loess samples from twenty-two typical Xiashu loess sections, using the major and trace element composition as a provenance indicator. Seventeen of the sites are located to the north of the Yangtze River and our primary aim was to determine the provenance of the Xiashu loess within this region. Our results indicate that the alluvial plain located mainly in the present drainage area of the Huai River was the primary dust source for the Xiashu loess in this region. The occurrence of multiple local dust sources within this alluvial plain, suggested by their geochemical heterogeneity, indicates that the alluvial plain experienced intensified aridity which caused it to become a dust source for local loess deposits in northern subtropical China during the Last Glacial. Our study provides strong evidence to challenge the long-held view that the occurrence of Xiashu loess resulted from the southward incursion of the CLP loess deposits sourced from deserts of the Asian interior, and it confirms the substantial role of aridification of the present humid northern subtropical region for dust emission to the climate system during the Last Glacial. Highlights: Major and trace element composition of samples from 22 Xiashu loess sections. The Xiashu loess was not primarily derived from the Asian interior deserts. Geochemical heterogeneity indicates local dust sources in the alluvial plain. Alluvial plain in northern subtropical China aridified during the Last Glacial.